2004
DOI: 10.1177/0020764004046074
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Social Variables Associated with Psychiatric and School-Related Indicators for Asian/Pacific-Islander Adolescents

Abstract: For Asian/Pacific-Islander youths, the quality of the social supports, including family relations, may be particularly important in the adolescents' adjustment. When examining school-related outcomes, demographic variables, with particular emphases on ethnicity and culture, must be considered. When developing and implementing prevention and intervention services and programs, consideration of family and ethnic-cultural influences should be taken into account, with further research needed in several related dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 24 publications
(21 reference statements)
0
21
2
Order By: Relevance
“…86 Hishinuma et al found family support, friends’ support, and number of relatives frequently seen to be protective against depression among AAs and NHPIs in Hawaii; as friends’ support increased, depressive symptoms decreased, except for Hawaiians. 88 Juang and Cookston found that higher levels of family obligation were associated with fewer depressive symptoms among Chinese American adolescents; increasing family obligation behaviors were associated with decreasing depressive symptoms over time. 89 Park (2009) found that parental care is negatively associated with depression among Korean adolescents, 90 and Qin et al found that family cohesion is protective of depression among Chinese adolescents.…”
Section: Question 4: What Protective Factors Exist To Buffer the Effementioning
confidence: 99%
“…86 Hishinuma et al found family support, friends’ support, and number of relatives frequently seen to be protective against depression among AAs and NHPIs in Hawaii; as friends’ support increased, depressive symptoms decreased, except for Hawaiians. 88 Juang and Cookston found that higher levels of family obligation were associated with fewer depressive symptoms among Chinese American adolescents; increasing family obligation behaviors were associated with decreasing depressive symptoms over time. 89 Park (2009) found that parental care is negatively associated with depression among Korean adolescents, 90 and Qin et al found that family cohesion is protective of depression among Chinese adolescents.…”
Section: Question 4: What Protective Factors Exist To Buffer the Effementioning
confidence: 99%
“…Lastly, as with adolescents from other ethnic and racial groups, peer influence has been cited as one of the strongest influences on Asian girls’ decisions to use substances (Adhikari, Chen, & Ahijevych, 2002; Iwamoto et al, 2011; Kim et al, 2002; National Asian Women’s Health Organization, 2000). Despite the seemingly detrimental effect of peer influence, however, literature has suggested that family support and parent-child attachment can override peer influence and protect adolescents from substance use (Au & Donaldson, 2000; Hahm, Lahiff, & Guterman, 2003; Hishinuma et al, 2004; Kim et al, 2002), indicating that substance use among Asian American adolescent girls may be prevented by increasing parental support and strengthening parent-child relationships.…”
Section: Factors Contributing To Substance Use Among Asian American Amentioning
confidence: 99%
“…Missing from the literature on overt aggression are studies that include sizable numbers of Hispanic adolescents and we know very little about symptom levels of aggression among this group. Including Hispanic adolescents in this body of research is particularly important given that previous research has found that ethnicity is the best predictor of school-related outcomes such as conduct infractions (Hishinuma et al 2004). …”
Section: Aggressionmentioning
confidence: 99%